The brain, biology and evolution in art and its communication. (26th March 2009) - Zaidel, Dahlia W.
Both art and language are referential and symbolic, but while quite a bit is known about language localisation in the brain, scant little is known about art in that regard. In neurology and neuropsychology, studies of patients with localised brain damage for over 100 years has helped chart the neuroanatomical underpinning of numerous types of cognition. Insight into the neuroanatomical underpinning of aspects of art can be obtained from professional artists who have suffered localised or diffuse brain damage. Similarly, artists with brain damage from birth, known as autistic savants, can provide further help in shedding light into brain and art. The origin of art practice in Homo sapiens existence is important in any discussion of brain and art, as is the relevance of biological motivation shared by animals and humans. These issues are discussed in this article.